A Study of the Effects and Policy Implications of Flat Rate Tuition - Keenan, Claudine; Chhatwal, Gurprit; Wang, Jinchang (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
In the current era of decreasingpublic funding and increasing pressure to improve student performance, many schools are considering or have implementedflat rate tuitionplans that allow students to take a higher course load for a fixed flat tuition. This study investigates the effects of flat rate tuition over the past eight years on course loads attempted by students, rate of withdrawal from classes,and four-year graduation rates ata four-year public college. This study shows that students are responsive to flat rate tuition,and flat rate tuition has had an overallpositive effect on students academic progress.